Experimental investigation of wing tip vortex - Elsayed, Omer Ali; Asrar, Waqar; Omar, Ashraf Ali; Kwon, Kijung; Jung, Hyejin (2009)
Particle image velocimetery was used in a low-speed wind tunnel to investigate and characterize wing tip vortex structures. A rectangular wing of a SWIM model was used as a vortex generator in two different configurations, (i) plain wing and (ii) flapped wing with trailing edge flap extended at 20 degrees. Vortex flow quantities and their dependence on angle of attack at a chord base Reynolds Number of 32.8x103 and 43.8x103 were evaluated. Assessment of measured data reveals that the peak values of tangential velocities, vortex strength and vorticities are directly proportional to the angle of attack. The vortex core radius value grows slowly as the angle of attack is increased. Both plain and flapped configurations showed similar trends. The peak tangential velocities and circulation distribution doubled when the flapped configuration was used instead of the plain wing.